Unveiling the Intersection of Psychology and Strategic Management in Human Resource Management: A Descriptive Inquiry with Literature Review - Pantih, Suwardhi (Manunggal Halim Jaya, 2024)
This study explores the intersection of psychology and strategic management in Human Resource Management (HRM), highlighting the complex dynamics underlying organizational behavior and performance. Through a comprehensive literature review, it becomes evident that integrating psychological insights with strategic management principles is essential for effectively understanding and managing human resources within organizations. From a theoretical perspective, this synthesis of literature contributes to the advancement of HRM theory by emphasizing the interconnectedness of psychological factors and strategic objectives. The recognition of the influence of individual and organizational dynamics underscores the need for holistic HRM approaches that consider both psychological principles and strategic imperatives. The findings of this study have significant implications for HRM practitioners and organizational leaders. It emphasizes the importance of aligning HRM practices with organizational goals and values. By understanding the psychological needs and motivations of employees, organizations can design HRM interventions that enhance employee engagement, satisfaction, and performance. Additionally, the recognition of contextual factors highlights the importance of flexibility and adaptability in HRM practices. This study also addresses the challenges and opportunities arising from digitalization, globalization, and workforce diversity, and how these trends can enhance HRM effectiveness and efficiency. By integrating psychology and strategic management, this research provides guidance for developing evidence-based HRM strategies that optimize organizational performance and promote employee well-being in an ever-changing business landscape.